2022
DOI: 10.3389/fnins.2022.807045
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Immediate Cortical Activation on Mirror Visual Feedback Combined With a Soft Robotic Bilateral Hand Rehabilitation System: A Functional Near Infrared Spectroscopy Study

Abstract: BackgroundMirror visual feedback (MVF) has been widely used in neurological rehabilitation. Due to the potential gain effect of the MVF combination therapy, the related mechanisms still need be further analyzed.MethodsOur self-controlled study recruited 20 healthy subjects (age 22.150 ± 2.661 years) were asked to perform four different visual feedback tasks with simultaneous functional near infrared spectroscopy (fNIRS) monitoring. The right hand of the subjects was set as the active hand (performing active mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…The upper limb rehabilitation robot glove and the bilateral motion caused by the MT optical illusion are perfectly combined to realize the "central-peripheral-central" closed-loop central control correlation. This mechanism is critical for poststroke patients, especially those with moderate to severe upper extremity motor dysfunction [29]. This is the theoretical support for our research.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The upper limb rehabilitation robot glove and the bilateral motion caused by the MT optical illusion are perfectly combined to realize the "central-peripheral-central" closed-loop central control correlation. This mechanism is critical for poststroke patients, especially those with moderate to severe upper extremity motor dysfunction [29]. This is the theoretical support for our research.…”
Section: Discussionsupporting
confidence: 82%
“…Third, based on the principle of bilateral training, the soft robotic glove realizes a bilateral movement training mode through the joint action of the affected hand, which is beneficial to the normalization of cortical inhibition between the cerebral hemispheres. Several studies have shown that bilateral training is superior to neurodevelopmental therapy and unilateral robotic-assisted training in improving upper extremity motor function after stroke [27][28][29][30][31]. Fourth, the linkage device of the robotic glove can easily realize the repetitive motion of the affected hand, continuously provide positive feedback to the central nervous system through peripheral motion (each 30 minutes, can complete 150-200 grasps), strengthen the neuronal circuit, thereby promoting neural remodeling of the affected brain.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that NMES+AO, NMES+AE, and NMES+AI all activated the brain areas, including the MNS, suggesting that the simultaneous application of NMES and AO, AE, or AI can improve the treatment effects by inducing cortex activation and neuroplasticity. According to the MNS theory, when participants observe the movements, the activation of MNS may induce automatic "imitation" in the brain unconsciously, resulting in a certain degree of pre-activation of the corresponding neural pathway controlling the movement of the target muscles, thereby exhibiting a positive impact on motor learning or function (35). In addition to brain activation, NMES and FES could also evoke muscle contraction, joint movement, and sensory input to the central nervous system, thus establishing a feedback loop (59,60).…”
Section: Activation Of Brain Areas During Neuromuscular Electrical St...mentioning
confidence: 99%
“…CBF increases in the stimulus/task state and decreases in the resting state, and fNIRS is used to evaluate CBF changes by the detection of blood-oxygen-level dependent (BOLD) optical signal changes. Compared with other brain functional imaging techniques, fNIRS has the following advantages: high temporal resolution (~10 Hz), good spatial resolution (2-3 cm), being non-invasive or non-traumatic, real-time monitoring, easy continuous and repeated measurement, low cost, miniaturization, portability, anti-motion artifacts, suitable for a wider range of individuals, and easy to combine with other techniques for multimodal functional imaging, including functional magnetic resonance imaging (fMRI), positron emission tomography (PET), magnetoencephalography (MEG), electroencephalography (EEG), event-related potential (ERP), or electromyography (EMG) (33,(35)(36)(37). fNIRS experiments can be carried out in the natural environment without constraints and large amplitude movement monitoring (38).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies using fMRI, TMS and EEG failed in showing a significant cortical activation related to MVF in healthy subjects [65][66][67][68][69] , a conspicuous amount of evidence demonstrated the central role of the sensory-motor cortex 27,51,53,57,58,61,[70][71][72][73][74][75] .…”
Section: Cortical Bases and Visuo-motor Theory Of Mvfmentioning
confidence: 99%